Hook removal from a loggerhead sea turtle (Caretta caretta) : Report of a tricky surgery under difficult conditions. - Barreiros, João P. (2015)
A sub adult Caretta caretta was found on the 23rd August, 2014 ca. 16 nautical miles south off S. Miguel Island, Azores (Northeast Atlantic), with a large pelagic trawl hook inside its mouth. The individual was kept in a basin of sea water and sent by boat to Terceira Island following instructions by the Azores Regional Government via the Environmental Authority in order to be examined by the author and, if possible, undergo the necessary hook removal procedures. In this note, we describe the surgical procedures and how the turtle was evaluated both pre- and post-surgery.